FKRP directed fibronectin glycosylation: A novel mechanism giving insights into muscular dystrophies?. (1st March 2022) - Boyd, Andrew; Montandon, Margo; Wood, Alasdair J.; Currie, Peter D.
Abstract: The recently uncovered role of Fukutin‐related protein (FKRP) in fibronectin glycosylation has challenged our understanding of the basis of disease pathogenesis in the muscular dystrophies. FKRP is a Golgi‐resident glycosyltransferase implicated in a broad spectrum of muscular dystrophy (MD) pathologies that are not fully attributable to the well‐described α‐Dystroglycan hypoglycosylation. By revealing a new role for FKRP in the glycosylation of fibronectin, a modification critical for the development of the muscle basement membrane (MBM) and its associated muscle linkages, new possibilities for understanding clinical phenotype arise. This modification involves an interaction between FKRP and myosin‐10, a protein involved in the Golgi organization and function. These observations suggest a FKRP nexus exists that controls two critical aspects to muscle fibre integrity, both fibre stability at the MBM and its elastic properties. This review explores the new potential disease axis in the context of our current knowledge of muscular dystrophies. Abstract : Muscular dystrophies associated with the Golgi resident glycosyltransferase FKRP have recently been shown to have a novel mechanism driven by non‐direct FKRP action. This review explores the impact of this finding on the mechanisms and pathology of both FKRP associated dystrophies and the muscular dystrophy field in general.